Identification of a major QTL underlying sugar content in peanut kernels based on the RIL mapping population - Wang, Feifei; Miao, Huarong; Zhang, Shengzhong; Hu, Xiaohui; Li, Chunjuan; Chu, Ye; Chen, Charles; Zhong, Wen; Zhang, Tianyu; Wang, Heng; Xu, Linying; Yang, Weiqiang; et al. (Frontiers in Plant Science, 2024)
High sugar content in peanut seeds is one of the major breeding objectives for peanut flavor improvement. In order to explore the genetic control of sugar accumulation in peanut kernels, we constructed a recombinant inbred line population of 256 F2:6-7 lines derived from the Luhua11 × 06B16 cross. A high-resolution genetic map was constructed with 3692 bin markers through whole genome re-sequencing. The total map distance was 981.65 cM and the average bin marker distance was 0.27cM. A major stable QTL region (qSCB09/qSSCB09) was identified on linkage group (LG) B09 associated with both sucrose content (SC) and soluble sugar content (SSC) explaining 21.51-33.58% phenotypic variations. This major QTL region was consistently detected in three environments and mapped within a physical interval of 1.56 Mb on chromosome B09, and six candidate genes were identified. These results provide valuable information for further map-based cloning of favorable allele for sugar content in peanut.